O processo de institucionalização de um sistema de planejamento governamental: o caso do Estado do Paraná - Jose, Herbert Antonio Age (1982)
The obj ecti ve of the present study is to fOnIr.l1ate an analysis of an experiment in government planning, through the application of the institution building model to the case of the state of Paraná. The author's choice of this theme is a result of a skeptical feeling towards government planning in the state leveI among the bureaucrats in Brazil. This feeling is due to the existence of an excessive centralization inthe public policy formulation process by the Federal Government, which centralizes even the main implementation instruments of such policies .. The second reason for the choice of this theme is the possibility of the planning experiment in Para ná State Government, in the 1975/1980 period, having been conducted as an exception to· this feeling. The basic theoretical framework used in the development of this study was the model formulated by Milton J. Esman and Hans C.Blaise of the Inter-University Research Program in Institution Building - IRPIB,led· by theUniversity of Pittsburgh. This model is based on the system analysis theory and, consequentely, regards organizations as open systems which are in permanent relationship with the enviro~ mente Therefore, the several variables analysed in the model are concentrated in the characterization of three basic elements: the organization, the environment and the linkages between both. The study is divided in to five chapters. In the first chapter the author introduces the theme and pointsout its importance, the objectives and the methodology followed. The second chapter describes the theoretical model and its applicability as a research guide in the organizationalfield and also reviews the most relevant bibliography on the subject. The third chapter presents a historical report on the governamental planning in Brazil and specifically in the State of Parana where the report evolves until the present organizational configuration of the State Planning· System. In the fourth chapter is related the application of the theoretical model, through the identification of the instit~ tional variables (leadership, doctrine, programs, resources and internaI structures), through the institucional environ mental linkages (enabling, normative, functional and diffused), and through the transactions. This allows us to reflect on the degree of institucionality of an organization. Finally, in the fifth chapt~r, general comments on the studied organism and on its perspectives are made.